Florida Crop/Pest Management Profile: Guava and Wax Jambu - Mark A. Mossler; Jonathan Crane (EDIS)
Revised! Circular 1415, a 6-page fact sheet by Mark A. Mossler and Jonathan Crane, profiles these tropical plants of the Myrtaceae family — production facts, regions, and practices; insect/mite, weed, disease, and nematode management; and key contacts. Includes references. Published by the UF Department of Horticultural Sciences, August 2009.